Macro nutrient status of Sundarbans forest soils in Southern region of Bangladesh - Khan, MZ; Amin, MS (Bangladesh Journal of Scientific and Industrial Research, 2019)
An attempt has been made to evaluate the condition of soil of the Sundarban mangrove forest of Bangladesh by applying standard method. Soil pH was varied from 6.63 to 7.87. Organic carbon of soil was found 4.06, 4.79, 5.59, 9.38 and 9.80 (gKg-1) at Kotka, Kochikhali, Hironpoint, Harbaria, and Dublarchar, respectively. The electrical conductivity of soil was varied from 14.39, to 42.89 (dSm-1) in the study areas.The cation exchange capacity in the soils was varied from 22.32 to 27.2 Cmolckg-1 in the study area. The average percentages of total nitrogen content in the soil were varied from 0.04 to 0.08%. The soils of Oligohaline zone of Sundarban mangrove forest are rich in water soluble and exchangeable magnesium followed by calcium and the potassium. The percentages of silt and clay were higher than sand in all study areas. Dissolved chloride in the soil was found 7010, 4186,11750 and 16389 (μg g-1) at Hironpoint, Harbaria, Dublarchar and Kotka respectively. Bangladesh J. Sci. Ind. Res.54(1), 67-72, 2019